Trust is essential: Identifying trust building techniques from youth providers across the service array. (October 2020) - Valenti, Michael; Celedonia, Karen L.; Wall-Parker, April; Strickler, Amy
Highlights: Diverse service providers identified components of trusting relationships. Providers assigned ratings of importance and experience with each technique. A five component framework for building trust with youth is introduced. Supervisors can support development of the skills and techniques identified here. Abstract: Past research has identified that a sense of mutual trust between providers and youths may be the most significant component of a strong working relationship. Service providers who successfully develop trust with youths they serve may achieve more desirable outcomes than providers who are unable to create a trusting relationship. This study used Group Concept Mapping to solicit the techniques and skills real providers use to build trust with youth across a diverse service array. Providers then rated each technique on importance for building trust, as well as their direct experience with the technique in practice. Results identified five overarching categories of trust building mechanisms service providers use across the child welfare spectrum. These findings can help provider organizations to focus training and supervisory efforts to help staff to build and maintain trusting relationships with youth.